Want this question answered?
Be notified when an answer is posted
x + 7y = 33 multiply through by 3: 3x + 21y = 99 Subtract the second equation from the above equation: 23y = 92 So y = 4 Substituting this value of y in the first equation, x + 28 = 33 ie x = 5 The solution is (x,y) = (5,4)
−39x−6
If: 3x+6 = 12 Then: x = 2
3x - 2 = 9 3x = 9 + 2 = 11 x = 11/3
It is not an equation and no solution is possible.
3x+5 Solution- 3x+5=0 3x= (-5) x= (-5)/3
x + 7y = 33 multiply through by 3: 3x + 21y = 99 Subtract the second equation from the above equation: 23y = 92 So y = 4 Substituting this value of y in the first equation, x + 28 = 33 ie x = 5 The solution is (x,y) = (5,4)
−39x−6
There is no solution since there is no equation, just an expression.
Solve 3x = 33
If: 3x+6 = 12 Then: x = 2
Assuming the equation is: 3x - 1 = 0 Then... 3x = 1 x = 1/3
If you mean: 3x-9 = 12 then the value of x is 7
1,2.5
A solution to an question makes the equation true. For example a solution to the equation 3x = x + 6 is x = 3, since 3(3) = 3+6.
3x - 2 = 9 3x = 9 + 2 = 11 x = 11/3
It has no solution and if you mean 4x+10+3x+40-3x then it can be simplified to: 50+4x _________________________________________________________________________________________ Assuming that the equation is 4x+10+3x+40-3x = 0, then it will reduces to 4x = - 50, then the answer is: x = -12.5